Wear intensity evaluation in conveying systems – An acoustic emission and vibration measurement approach. (September 2020) - Varga, Markus; Haas, Michael; Schneidhofer, Christoph; Adam, Karl
Abstract: Conveying raw materials is essential in heavy industries and mostly accompanied by wear. Impinging of materials cause energy transfer, generating elastic waves. In this work, an acoustic emission (AE) measurement system and an accelerometer for vibrations were utilised to assess different wear phenomena. A 3-fold approach was undertaken: i) identification of characteristic acoustic damage features in a model impact-test; ii) impact tests with raw materials on wear plates in lab-scale; iii) field test of the measurement systems in the harsh environment of a steel plant. Results showed clear frequency changes with decreasing plate thickness. Micro-cracking was indicated by high frequencies, showing the first stage of wear. AE and vibration measurements distinguished raw materials clearly in both, close-to-reality and field testing. Highlights: Acoustic emission and vibration measurements were used to determine wear intensity. Laboratory and field tests at a conveying system proofed the applicability of the system. A frequency spectrum indicating crack initiation in wear plates was identified. Acoustic signals were able to discriminate different impacting raw materials. The current state of wear can be derived from changing neutral frequencies.